2017
DOI: 10.1002/cctc.201601479
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Carbon‐Supported Pt–YOx and PtY Nanoparticles with High Catalytic Activity for the Oxygen Reduction Reaction Using a Microwave‐based Polyol Method

Abstract: Carbon‐supported PtY alloy nanoparticles were prepared as oxygen reduction reaction (ORR) catalysts by reducing a mixture of cis‐[Pt(NH3)2(NO2)2] or Pt(C5H7O2)2 and Y(CH3COO)3⋅4 H2O in ethylene glycol (EG) with microwave (MW) heating. Microstructure and composition analyses of products by using TEM, TEM–energy‐dispersive X‐ray spectroscopy (EDS), XRD, X‐ray photoelectron spectroscopy (XPS), and inductively coupled plasma atomic emission spectroscopy (ICP‐AES) data showed that Pt–YOx/C (Y/Pt=0.11–0.75) catalyst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Many attempted to chemically synthesized these nanoparticles [28][29][30][31][32][33][34] , but without showing any real evidence of Pt-Y alloy formation, i.e. x-ray diffraction spectrum only showing Pt peaks and/or no x-ray photoelectron spectroscopy analysis of the Y 3d region.…”
Section: Introductionmentioning
confidence: 99%
“…Many attempted to chemically synthesized these nanoparticles [28][29][30][31][32][33][34] , but without showing any real evidence of Pt-Y alloy formation, i.e. x-ray diffraction spectrum only showing Pt peaks and/or no x-ray photoelectron spectroscopy analysis of the Y 3d region.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that microwave (MW) heating is effective for the preparation of metallic catalysts on supports such as carbons and TiO 2 . Because carbons and metallic particles with conductive electrons absorb MW efficiently, metallic catalysts are locally heated and adsorbed strongly to support.…”
Section: Introductionmentioning
confidence: 99%
“…c) Comparison of the peak temperatures among various masses of carbon black (20, 200, and 800 mg) during microwave irradiation. d) Comparison of the heating times and temperatures demonstrated in this work with previous carbon‐black‐based microwave syntheses …”
Section: Resultsmentioning
confidence: 94%
“…Recently, microwave‐assisted synthesis has been extensively studied in carbon‐based composites . By using liquid‐phase microwave heating strategy, carbon‐supported metal, alloy and metal chalcogenide nanoparticles have been successfully fabricated, resulting in homogeneous and well‐defined nanoparticle catalysts that demonstrated enhanced performance for fuel cell applications. However, these liquid‐phase synthetic processes suffer many of the same pitfalls as that of conventional wet chemistry methods.…”
Section: Introductionmentioning
confidence: 99%